2019
DOI: 10.1002/ece3.5503
|View full text |Cite
|
Sign up to set email alerts
|

DNA metabarcoding adds valuable information for management of biodiversity in roadside stormwater ponds

Abstract: Stormwater ponds are used to compensate for the adverse effects that road runoff might have on the natural environment. Depending on their design and placement, stormwater ponds can act as both refugia and traps for local biodiversity. To evaluate the impact of stormwater ponds on biodiversity, it is critical to use effective and precise methods for identification of life associated with the water body. DNA metabarcoding has recently become a promising tool for identification and assessment of freshwater biodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 56 publications
3
17
0
Order By: Relevance
“…Our results are in accordance with several other studies that also identified more species with eDNA compared with other conventional methods in different ecosystems (e.g., Andruszkiewicz et al., 2017; Civade et al., 2016; Handley et al., 2019; Valentini et al., 2016). In addition, eDNA metabarcoding detected 72% of species captured by trawling, which is also congruent with previous comparative studies showing that eDNA detects between 60% and 100% of the species that were detected by other conventional methods (e.g., Fujii et al., 2019; Shaw et al., 2016; Sun et al., 2019; Thomsen et al., 2016; Valentini et al., 2016; Yamamoto et al., 2017). Here, it should be noted that eDNA lower detection of species that were observed by conventional methods could be explained by different sampling efforts.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our results are in accordance with several other studies that also identified more species with eDNA compared with other conventional methods in different ecosystems (e.g., Andruszkiewicz et al., 2017; Civade et al., 2016; Handley et al., 2019; Valentini et al., 2016). In addition, eDNA metabarcoding detected 72% of species captured by trawling, which is also congruent with previous comparative studies showing that eDNA detects between 60% and 100% of the species that were detected by other conventional methods (e.g., Fujii et al., 2019; Shaw et al., 2016; Sun et al., 2019; Thomsen et al., 2016; Valentini et al., 2016; Yamamoto et al., 2017). Here, it should be noted that eDNA lower detection of species that were observed by conventional methods could be explained by different sampling efforts.…”
Section: Discussionsupporting
confidence: 88%
“…Sun et al. (2019) demonstrated that DNA metabarcoding may identify more than twice the number of taxa compared with net‐based morphological identification methods. Altogether, these findings strongly suggest that eDNA at the very least offers similar but often higher performance of detection than those traditional methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the finding that all 39 records with partial DNA barcodes (29 <400 bp; 10 <500 bp) have been assigned successfully to a conspecific BIN cluster ( Supplemental File S3 ) demonstrates that ‘minibarcodes’—more suitable for metabarcoding-based community assessments—have the potential to correctly identify Odonata DNA traces. This finding is in line with several recent studies employing partial COI-based DNA metabarcoding for freshwater community assessments (e.g., Sun et al, 2019 ; Zizka, Geiger & Leese, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…Work has also been done in ocean systems with studies ranging from examining shark diversity response to anthropogenic disturbance to understanding how anthropogenic activities such as oil spills and development impact micro and macro coastal communities (Bakker et al, 2017;Xie et al, 2018;DiBattista et al, 2020). Sun et al (2019) used eDNA metabarcoding to understand Dipteria and other organism populations in human caused roadside stormwater ponds. Additionally, Klymus et al (2017) examined how anthropogenic uranium containment ponds impacted the biodiversity of vertebrate species.…”
Section: Introductionmentioning
confidence: 99%